2019
DOI: 10.1002/jmri.26960
|View full text |Cite
|
Sign up to set email alerts
|

Prostate diffusion MRI with minimal echo time using eddy current nulled convex optimized diffusion encoding

Abstract: Background: Prostate diffusion-weighted imaging (DWI) using monopolar encoding is sensitive to eddy-current-induced distortion artifacts. Twice-refocused bipolar encoding suppresses eddy current artifacts, but increases echo time (TE), leading to lower signal-to-noise ratio (SNR). Optimization of the diffusion encoding might improve prostate DWI. Purpose: To evaluate eddy current nulled convex optimized diffusion encoding (ENCODE) for prostate DWI with minimal TE. Study Type: Prospective cohort study. Populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additional technical improvements continue to emerge in the field, including improved fat suppression, 56 and eddy current suppression with optimized gradients. 110,111 These methods continue to advance diffusion MRI toward the goal of enabling reliable, artifactfree imaging, as required for precise quantification.…”
Section: Other Image Acquisition Developmentsmentioning
confidence: 99%
“…Additional technical improvements continue to emerge in the field, including improved fat suppression, 56 and eddy current suppression with optimized gradients. 110,111 These methods continue to advance diffusion MRI toward the goal of enabling reliable, artifactfree imaging, as required for precise quantification.…”
Section: Other Image Acquisition Developmentsmentioning
confidence: 99%
“…One such approach is employing an optimized encoding scheme to ensure the preservation of SNR, even when a reduced number of averages is acquired. Zhang et al hypothesize that fewer averages can be acquired for DWI while maintaining sufficient SNR, by adjusting magnetic gradients for an optimized diffusion encoding scheme that is capable of suppressing eddy current‐induced distortion artifacts and facilitating improvement in SNR for a given b ‐value and EPI readout duration 39 . In this study, carried out prospectively on 10 volunteers, 5 patients, a phantom, and an ex‐vivo prostate specimen to compare the optimized diffusion encoding to conventional unipolar and bipolar encoding schemes, three radiologists found that the optimized encoding scheme demonstrated ≥25% higher SNR and had similar or higher image quality compared to bipolar encoding while also reducing eddy current effects.…”
Section: Resultsmentioning
confidence: 99%